2012
DOI: 10.1590/s1984-29612012000300010
|View full text |Cite
|
Sign up to set email alerts
|

Experimental infection with Neospora caninum in pregnant bitches

Abstract: In this study, transplacental transmission of Neospora caninum in bitches at different stages of pregnancy was evaluated. Three bitches were inoculated in the 3 rd week and three in the 6 th week of gestation with 10 8 tachyzoites of N. caninum (Nc-1 strain). All the infected bitches and at least one of their offspring presented anti-N. caninum antibodies according to the indirect fluorescent antibody test (IFAT ≥ 400). The pups and their mothers were sacrificed and tissues from the central nervous system (CNS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Cavalcante et al (2012) confirmed transplacental transmission of N. caninum in dogs. Six bitches in two groups were inoculated with a very high dose (10 8 tachyzoites).…”
Section: Transmissionmentioning
confidence: 73%
“…Cavalcante et al (2012) confirmed transplacental transmission of N. caninum in dogs. Six bitches in two groups were inoculated with a very high dose (10 8 tachyzoites).…”
Section: Transmissionmentioning
confidence: 73%
“…Hindlimb paralysis, myositis, or both are most commonly reported, reflecting the neuromuscular tropism seen in intermediate hosts . Transplacental transmission has been demonstrated in experimental infection, and affected tissues from these puppies include the heart, lungs, abdominal viscera, and various neurologic tissues . It is not clear whether natural infections in puppies arise mainly through transplacental or transmammary infection, however, or whether young dogs are susceptible to infection from oocysts when adult dogs seem not to be.…”
Section: Life Cycles Of the Sarcocystidae In Dogs And Catsmentioning
confidence: 99%
“…Although no association was found between the variables of urban/rural environment and the prevalence of the two agents, associations were found between several other variables. The association between young aged animals and seropositivity for N. caninum in dogs appears to suggest possible transplacental transmission (Cavalcante et al, 2012), which is also supported by the non-hunting behavior of many of these dogs. In contrast, an association was found between older dogs and the prevalence of T. gondii, indicating that the dogs in this region were exposed to this coccidian parasite for longer periods of time during their life, which suggests that the main route of infection in dogs is horizontal transmission (Cañón-Franco et al, 2003;Cano-Terriza et al, 2016).…”
Section: Resultsmentioning
confidence: 80%